ANALISIS KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA PESERTA DIDIK KELAS XII SMAN 1 SIPORA KABUPATEN KEPULAUAN MENTAWAI MENGGUNAKAN PROBLEM BASED LEARNING - Delia, Lora; Rahmi, Rahmi; Hamdunah, Hamdunah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low mathematical problem-solving ability of students. The purpose of this study is to determine the mathematical problem-solving ability of class XII students of SMAN 1 Sipora, Mentawai Islands Regency through the application of the Problem Based Learning (PBL) model. This research was conducted at SMAN 1 Sipora, Mentawai Islands Regency on July 28 to August 22, 2025. The subjects of this study were students of class XII F-3 as a trial class and class XII F-1 as a research class in the 2025/2026 academic year. The type of research used is experimental research with a posttest only control-group design. The data collection method used in this study is a final test and documentation. The results of the study indicate that the application of the Problem Based Learning model which is carried out based on the PBL steps, which refer to indicators of problem-solving ability, namely understanding the problem, making a solution plan, implementing the solution, and seeing and re-examining, is able to improve students' mathematical problem-solving ability. Based on the problem-solving ability indicators on the Student Worksheet (LKS) of the second meeting, overall students have fulfilled the problem-solving ability indicators, namely: (1) understanding the problem, (2) making a problem-solving plan, and (3) implementing the problem-solving plan. Students have generally been able to understand the problem and formulate a solution plan, although there are still some students who have not been optimal in the indicators of understanding the problem and making a problem-solving plan.